"Hope For The Hopeless": The coping mechanisms of father-daughter incest survivors / Umi Nurul Najihah Azman ... [et al.] - Najihah Azman, Umi Nurul; Ahmad, Yarina; Tahir, Nor Suziwana; Abd Hamid, Siti Nur Fathanah (2021)
Incest is categorised as a long-standing issue in the Malaysian context, which involves children under the age of 18 years old. The seriousness of the incest issue and its negative implications are undeniable. Among the negative implications of this issue are stress, mental health issue, psychological and physical damage, and in the worst scenario, some of the victims have committed suicide. Due to this situation, this paper presents a website called "Hope for the hopeless" which aims to serve as a platform to communicate, share information and stories with the victims and survivors of the incest issue. This will help to ease their burden and further help others who faced a similar situation. The development of this website benefits not only the targeted groups such as children and relevant agencies, but it also aims to share the research information with the public. Among the uniqueness of this product are: (1) website is originally developed on empirical evidence; (2) utilize the technology; (3) among the earliest works focused specifically on incest issue; (4) enhance child protection and privacy. The development of this product can be used as (1) a platform to communicate and share information; (2) a coping mechanism for incest victims and survivors; (3) a channel of information to relevant agencies; (4) national policies; and (5) international policies. Thus, with the existence of this website, the victim and the survivors of the incest issue can find the right coping mechanism to reduce their stress and cope with the problem.